2013
DOI: 10.7883/yoken.66.323
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Multiresistant OXA-24- and OXA-51-Producing <i>Acinetobacter baumannii</i> in an Internal Medicine Ward

Abstract: SUMMARY:Here we describe the clinical, microbiological, epidemiological, and molecular characterization of an outbreak of multidrug-resistant Acinetobacter baumannii (MRAB) involving 5 patients admitted to the internal medicine ward of our hospital. Over a 6-week period, 5 MRAB isolates were recovered from 5 patients, including 1 with fatal meningitis, 3 with skin and soft tissue infections, and 1 with respiratory colonization. One sample obtained during environmental monitoring in the ward was A. baumannii-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(20 reference statements)
1
9
1
Order By: Relevance
“…However, they cannot identify newly emerging multidrug-resistant epidemic clones that might spread in the future. In fact, multidrug-resistant isolates other than the A. baumannii international clones have been reported (12)(13)(14)(15)(16)(17)(18). The POT method constructed in the present study is applicable to the identification of new CCs of A. baumannii or A. calcoaceticus-A.…”
Section: Discussionmentioning
confidence: 80%
“…However, they cannot identify newly emerging multidrug-resistant epidemic clones that might spread in the future. In fact, multidrug-resistant isolates other than the A. baumannii international clones have been reported (12)(13)(14)(15)(16)(17)(18). The POT method constructed in the present study is applicable to the identification of new CCs of A. baumannii or A. calcoaceticus-A.…”
Section: Discussionmentioning
confidence: 80%
“…They concluded that environmental contamination has an important reservoir role in outbreaks of A. baumannii in ICUs. Results of Tena et al [ 25 ] showed that all five clinical isolates and one environmental isolate belonged to a single clone. Based on the clonal relationship of the isolates by pulsed-field gel electrophoresis (PFGE), they concluded that the infection source has probably been the hands of the healthcare workers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of Tena et al [ 25 ] showed that all five clinical isolates and one environmental isolate belonged to a single clone. Based on the clonal relationship of the isolates by pulsed-field gel electrophoresis (PFGE), they concluded that the infection source has probably been the hands of the healthcare workers [ 25 ]. Similarly, Cicek et al [ 7 ] suggested that all the patients and environmental isolates were derived from a common source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCWs were considered to be the actual source of the nosocomial outbreak in 35 [ 10 44 ] of the 1002 reports (= 3.6%) by the authors of the articles. However, we had to exclude 10 [ 10 , 13 , 16 , 18 , 19 , 28 , 30 , 35 , 42 , 44 ] articles after full text reading because they either provided insufficient evidence, had a general lack of data, took place at facilities other than hospitals (e.g., long term care facilities), or did not focus on GNB in particular. The colonisation status of the HCWs in the remaining 25 articles were either transient (11 articles) or permanent (14 articles).…”
Section: Resultsmentioning
confidence: 99%